Estimation of the Genome-Wide Mutation Rate and Spectrum in the Archaeal Species Haloferax volcanii. Issue 4 (1st August 2020) - Kucukyildirim, Sibel; Behringer, Megan; Williams, Emily M; Doak, Thomas G; Lynch, Michael
Abstract: Organisms adapted to life in extreme habitats (extremophiles) can further our understanding of the mechanisms of genetic stability, particularly replication and repair. Despite the harsh environmental conditions they endure, these extremophiles represent a great deal of the Earth's biodiversity. Here, for the first time in a member of the archaeal domain, we report a genome-wide assay of spontaneous mutations in the halophilic species Haloferax volcanii using a direct and unbiased method: mutation accumulation experiments combined with deep whole-genome sequencing. H. volcanii is a key model organism not only for the study of halophilicity, but also for archaeal biology in general. Our methods measure the genome-wide rate, spectrum, and spatial distribution of spontaneous mutations. The estimated base substitution rate of 3.15 × 10 −10 per site per generation, or 0.0012 per genome per generation, is similar to the value found in mesophilic prokaryotes (optimal growth at ∼20–45°). This study contributes to a comprehensive phylogenetic view of how evolutionary forces and molecular mechanisms shape the rate and molecular spectrum of mutations across the tree of life.